Pengaruh Motivasi Dan Kemampuan Serta Komitmen Terhadap Kinerja Pengurus Upk Pnpm Mandiri Perdesaan Di Kabupaten Lumajang - Kasno T.Kasim (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
This study aims to determine the influence of motivation and ability and commit- ment as well as simultaneous and partial view of the dominant of the Performance Management UPK PNPM Mandiri Rural In Lumajang of 60 respondents. The hypothesis in this study is the motivation and the ability and commitment to si- multaneously have a significant effect on the performance committee UPK PNPM Mandiri Rural on Lumajang. Motivation and the ability and commitment partially significant effect on the performance committee UPK PNPM Mandiri Rural Dis- trict Lumajang.Variabel motivation dominant influence on the performance com- mittee UPK PNPM Mandiri Rural on Lumajang. The results of this study indicate: 1). Fcount value of 18.274 while the value of 2.769431 Ftable with probability = 0.000 when compared then Fcount > Ftable with α <0.5, then reject or accept Ho Ha. Coefficient of determination R-square value is equal to 0.495, which means that approximately 49.5% of the motivational variables (X1) and ability (X2) and commitment (X3) jointly have a significant influence on performance (Y). 2). Val- ue of 3.372 Ttable Tcount X1 = 2.003 with a probability of 0.001. Value of 2.087 Ttable Tcount X2 = 2.003 with a probability of 0.041. Value of 2.473 Ttable Tcount X3 = 2.003 with a probability of 0.016. Because Tcount > Ttable and a significance level of α <5%, then the partial variables X1 and X2 and X3 affect significantly on the performance variable (Y). Thus Ho, Ha is rejected or accepted. 3). Based on the analysis of each variable indicates standardized regression coefficients of the regression coefficient of 36.9% Motivation β1, β2 Traffic of 23.5%, 27.9% Commitment β3 or β1> β3> β2 thus dominant influence motivational variables on performance. This quantitative study provides an overview of the importance of motivation and the ability and commitment to improving employee performance. If the motivation and the ability and commitment to get less attention then it will be a decrease in employee performance.